Introduction: A Literary Studies/Games Studies Conversation. Issue 7 (3rd November 2019) - Hutton, Margaret-Anne; Barr, Matthew
In this special issue of Games and Culture, we present papers originally delivered at the "Literature and Video Games: Beyond Stereotypes" event co-organized by colleagues from the University of St Andrews, the University of Glasgow, and Abertay University. Instead of gesturing toward a summary and synthesis of the published articles, we invite readers to consider these in light of the issues raised in this Introduction, which is itself a very condensed version of many exchanges between the coeditors.